PERANCANGAN MESIN PENGGORENG DAN MESIN PENGADUK BUMBU PANTIAW - Muhammad Rizki; Helvana; Idiar Idiar; Somawardi Somawardi (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Pantiaw is a typical food originating from Bangka Belitung. The marinade is made from fish and a mixture of other ingredients such as coriander, soy sauce, salt and other flavorings, however, for the process of stirring the pantiaw seasoning, it still uses the manual method. To simplify the process of stirring the pantiaw seasoning, a design for the pantiaw spice mixer was made with a capacity of 10 kg, as well as the SOP (Standard Operating Procedure) and the machine maintenance system, a research method was needed. The method used is the VDI 2222 method which consists of 4 stages, namely planning, conceptualizing, designing, completing. The results of this design process obtained a variant of concept III with a percentage of the technical aspect assessment of 80% and the percentage of economic assessment of 100%. The results of the calculation of the container capacity of 21 kg using a motor power engine of 1 Hp with 1400 rpm, and using a pulley and V-belt belt type A with a shaft diameter of 32 mm and a v-belt length of 1321 mm. The maximum stress that occurs on the shaft diameter of 25 mm is 5 x 10-1 N/mm2